Irritable bowel syndrome (IBS) - Quigley, Eamonn M. M. (Henry Stewart Talks, 2011)
A common symptom-based disorder which affects 5-15% of the adult population world-wide, For some, symptoms can be severe, frequent and significantly impact on quality of life, Commonly regarded as reflecting a dysfunction of the gut-brain axis, low grade inflammation and dysbiosis of the microbiota have been implicated of late, Management continues to be challenging with approaches which aim to alleviate individual symptoms (pain, constipation, diarrhoea) continuing to dominate in the absence of truly disease-modifying therapies.